Analysis of difference in service quality, food quality and santri satisfaction levels in city and village boarding school - Chairunissa Aulia Zikrika; Putri Ronitawati; Prita Dhyani Swamilaksita; Mertien Sa'pang; Harna Harna (Darussalam Nutrition Journal, 2021)
Background: Islamic boarding schools in Indonesia have a classic problem, namely health problems. And the health problem itself rarely gets the attention of the boarding schools and the government. One of the foods for teenagers who live in the hostel is the food that is not according to taste. Therefore, food intake is reduced, resulting in malnutrition problems among adolescents who live in dormitories, so in an institution it is necessary to organize food that meets the recommended standards and adequacy, and pay attention to taste and appearance. Objective: to find out the differences in the service quality, food quality and the satisfaction level of students in city and village Islamic boarding schools. Methods: study was a survey research cross sectional design in which the independent and dependent variables were observed and measured at the same time. to learn between the independent and the dependent variable, by giving filling in a check list or collecting data with an attachment to find out the differences between these variables. Result: food quality Sig. (2-tailed) 0,000 service quality Sig. (2-tailed) 0.235 satisfaction level Sig. (2-tailed) 0.116. For each indicator on the quality of food and service, respondents at the village boarding schools are more satisfied than the urban boarding schools. Conclusion: There are differences in food quality at city and village Islamic boarding schools , there is no difference between  quality of service and  level of satisfaction of the students at city and village  Islamic boarding schools. The two Islamic boarding schools should further improve service quality and food quality in order to further increase the satisfaction level of the students.